2009
DOI: 10.4161/auto.5.2.7360
|View full text |Cite
|
Sign up to set email alerts
|

Platonin induces autophagy-associated cell death in human leukemia cells

Abstract: Platonin is a photosensitizer used for photodynamic therapy. In this study, we tested the effect of platonin on human leukemic cells. Treatment with platonin in the dark markedly reduced cell membrane integrity, and induced significant G 0 /G 1 arrest of a panel of human leukemic cell lines, including U937, HL-60, K562, NB4 and THP-1. Development of hypodiploid cells was not evident in these cell lines within 24 h, but was noted in U937, HL-60 and NB4 cells after 24 h. No myeloid differentiation of these cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
0
37
1
1
Order By: Relevance
“…39,40 Accumulating anticancer agents have been documented to trigger the cellular autophagic process, but the role that autophagy plays in cancer chemotherapy is still controversial. Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Accumulating anticancer agents have been documented to trigger the cellular autophagic process, but the role that autophagy plays in cancer chemotherapy is still controversial. Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In animal cells, the components required for these phases are regulated by extracellular growth factors, and they are found mainly in the two gap phases, G 1 (between M and [25] . Platonin has been reported to induce significant G 0 /G 1 arrest of a panel of human leukemic cell lines, including U937, HL-60, K562, NB4, and THP-1 [16] . In this study, we also found that the loss of the proliferative capacity of VSMCs that had been treated with platonin is associated with cells that have been arrested in the S and G 2 /M phases.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory mechanisms of platonin may be due to the suppression of MAPKs, nuclear factor (NF)-魏B, and activator protein (AP)-1 [15] . Recently, platonin was also reported to be capable of inhibiting cell growth and inducing extensive autophagyassociated cell death in leukemic cells [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Glucocorticoids such as dexamethasone also contributed to autophagic death in leukemia of lymphoid origin [85,86]. In addition to these compounds, platonin, a photosensitizing compounds used in photodynamic therapy, was also found to induce cell death in several leukemic cell lines independent of the caspase pathway as is characteristic of autophagy [87]. In another study, autophagy was shown to be an important mechanism for cell death due to extensive recycling of cellular organelles damaged from photodynamic therapy in mouse lymphocytic leukemia cells [88].…”
Section: Contribution Of Autophagy To Cell Deathmentioning
confidence: 99%